Structural brain connectivity of HIV-positive children: a graph network analysis study - Fouche,Jean-Paul (Department of Psychiatry and Mental Health, 2022)
Vertical transmission of human immunodeficiency virus (HIV) from mother to child is a major problem in sub-Saharan Africa. As in adults, a variety of cognitive impairments may be evident in HIV infected children being treated with combined antiretroviral therapy (ART). The HIV virus compromises visual perception, attention, memory, language and executive functioning. Prior imaging studies have shown abnormal brain structure in adults and children infected by HIV. Graph theory analyses have been applied to HIV neuropathogenesis previously, these have demonstrated significant disruptions to brain connectivity in older HIV+ adults on treatment. However, no previous studies have investigated the same topological organization or structural connectivity of brain structure in infected children, or correlated this with markers of disease severity. The aims of this project were first, to delineate the topological organization of brain structure in children living with HIV currently on treatment and contrast it with healthy HIV negative children, second to investigate differences in measures of brain structure between healthy controls and children living with HIV and third to correlate brain imaging measures with markers of disease severity. The studies presented here examine the structural connectivity between nodes in the brain by utilizing magnetic resonance imaging and graph theory methods, and also investigated gray matter structure and cortical complexity. Children living with HIV displayed abnormal structural connectivity in regions of the dorsal posterior cingulate and inferior frontal gyrus of the frontal lobe, as well as in superior regions of the temporal lobe when compared to healthy HIV negative children. Significantly decreased cortical thickness was found in precentral and postcentral regions and the superior and middle frontal regions of children living with HIV compared to the healthy group. Deficits in cortical complexity of the inferior frontal gyrus and fusiform gyri were also apparent in the HIV infected group. Cortical thickness, surface area and gyrification were positively associated with CD4 count as a marker of disease severity. In conclusion, this project demonstrated abnormal brain structure and structural connectivity of brain structure in regions involved with motor development, executive function, and language fluency and generation in treated children living with HIV. Abnormal structural connectivity may indicate disruption to brain network integrity in developing children. Even in the post-ART era, infected children remain at risk for abnormal brain development. Longitudinal studies in larger cohorts are needed to address the issue of changes in brain structure and topology over time during adolescent brain development.